الرقابة من وجهة النظر الإسلامية في المؤسسات التعليمية الليبية: THE CENSORSHIP FROM THE ISLAMIC PERSPECTIVE IN THE LIBYAN EDUCATION INSTITUTIONS - Almaghrabi, Albarani Fathalla Mansour; Lubis , Asmuliadi; Sarif, Suhaili bin (Online Journal of Islamic Management and Finance (OJIMF), 2021)
This study aims to identify the censorship from Islamic perspective. The problem is there is less concern about using facilities censorship as Allah said in AlQuran and Sunnah. There is lack of using the Islamic perspective of censorship and recreate human behaviour that may negatively effects of the Libyan educational institutions. The importance of the study is to highlight the importance of Islamic perspective of censorship and work with the order of what Allah said for submitting work with highly efficiency to gain Allah satisfaction. This study follows descriptive and analytical to describe and analyse the censorship from the Islamic perspective. This study has several results, the censorship from Islamic perspective in achieving to reduce the financial and administrative corruption in the Libyan educational institutions. This study recommended to use the simulation idea to implement the successful experience from any Islamic country to use the censorship from Islamic perspective. This study also recommended to highlight the fear from Allah without delaying or corruption of the work inside Libyan intuitions.